Socio-Cultural Relations Between India and Indonesia - Mohd Tahseen Zaman (Proceeding Of The International Seminar and Conference on Global Issues, 2015)
India and Indonesia are two nations that from its inception, have a strong historical relation; cultural as well as intellectual. Both have some in common and similarities in many aspects. In India and Indonesia there are multiple religions, beliefs, ethnicities, languages, cultures that share and interact each other. The most interesting thing is both have shared cultural relations manifested in daily life. Some historians assumed that India’s influence on Indonesian’s culture is quite dominant, moreover, until the nineteenth century the Malay people received everything from India: their religion, their political system, astrology, medicine, literature, art and technical skills. Therefore this study is basically based on historical investigation and focuses on cultural analysis between Indonesia and India. Keywords: culture, shared, inception, ties